2014
DOI: 10.1177/2325967114528862
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Disc Degeneration and Spondylolysis in the Lumbar Spine of Professional Beach Volleyball Players

Abstract: Background:Beach volleyball is an intensive sport with high impact on the lumbar spine. Low back pain (LBP) is frequent among elite players. Increased prevalence of pathological changes on magnetic resonance imaging (MRI) in the lumbar spine of elite athletes has been reported. Hypothesis: There is an increased prevalence of disc degeneration and spondylolysis in the MRI of the lumbar spine of professional beach volleyball players.Study Design:Cross-sectional study; Level of evidence, 3.Methods:Twenty-nine ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
5
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 40 publications
(65 reference statements)
6
31
5
3
Order By: Relevance
“…Our study found a high number of lesions in soccer practitioners probably due to the high sensitivity of MRI for the detection of lesions-this is in contrast to most other studies that did not use MRI [16,22,33].…”
Section: Discussioncontrasting
confidence: 95%
“…Our study found a high number of lesions in soccer practitioners probably due to the high sensitivity of MRI for the detection of lesions-this is in contrast to most other studies that did not use MRI [16,22,33].…”
Section: Discussioncontrasting
confidence: 95%
“…Although lumbar disc degeneration is a common imaging finding in asymptomatic and symptomatic young individuals, our study showed that Olympic athletes have higher prevalence of moderate to severe disc degeneration than nonathletes [14,[29][30][31]. Even with the wide variation related to sample sizes, different age ranges, different clinical presentation, and different criteria and classification of the degenerative changes, our results are in accordance with several prior studies that showed the higher rate of these degenerative changes of the lumbar spine in athletes [1,2,6,[32][33][34][35]. For instance, Ong et al studied the degenerative changes in elite athletes with lower back pain at the Sydney 2000 Olympic Games and showed degenerative changes of 36% of the discs at the L5/S1 level which is comparable to our study [6].…”
Section: Discussionsupporting
confidence: 91%
“…All of these sports have been associated with quite a high prevalence of lumbar DD. 6,7,9,14,15,[17][18][19][20]23,[34][35][36] One of the more popular sports in Finland-football-has been previously associated with presacral DD, 23 but in our cohort, football was not associated with lumbar DD. Our questionnaire on participation to different sports included the most popular sports among young Finns in 1997-1998.…”
Section: Discussioncontrasting
confidence: 49%